DETECTION OF LATENT TUBERCULOSIS INFECTION IN HAEMODIALYSIS PATIENTS: A SYSTEMATIC REVIEW - Hamidah Retno Wardani; Damon Wicaksi (UNEJ e-Proceeding, 2020)
Background: Patients with end-stage renal disease (ESRD) undergoing hemodialysis are at risk of developing active TB 6 to 25 times higher than the general population. The importance of screening tuberculosis infection using diagnostic tests such as the Tuberculin Skin Test (TST) and QuantiFeron TB-Gold (QFT-G) and proper treatment in hemodialysis patients can prevent the increase of LTBI to active TB. Purpose: To determine the prevalence of Latent Tuberculosis Infection (LTBI) cases in hemodialysis patients using the Tuberculin Skin Test (TST) and Quantiferon TB-Gold (QFT-G). Methods: A Systematic Review study to determine the prevalence of LTBI in hemodialysis patients using the Prefered Reporting Items for Systematic Review and Meta-analysis (PRISMA) protocol. Results: Derived from 67 related articles and obtained 4 articles using the Randomized Control Trial (RCT) which met the criteria involving 516 ESRD patients undergoing hemodialysis. The study showed that the prevalence of LTBI using the diagnostic Tuberculin Skin Test (TST) (cut off ≥ 10 mm) and QuantiFERON-Tuberculosis Gold (QFT-G) showed TST + / QFT + 68 patients (18.47%), TST + / QFT- 22 patients (5.97 %), TST- / QFT + 77 patients (20.92%). Conclusion: This study shows a high prevalence of LTBI in hemodialysis patients. Screening and treatment of LTBI should be performed in hemodialysis patients to prevent the progression of LTBI to active TB. Keyword: Latent tuberculosis infection, hemodialysis, TST, QFT-G, ESRD.